Integrated systematic approach increase greenhouse tomato yield and reduce environmental losses. (15th July 2020) - Wang, Xiaozhong; Zhao, Mingjiong; Liu, Bin; Zou, Chunqin; Sun, Yixiang; Wu, Gang; Zhang, Qian; Jin, Guoqing; Jin, Zhenghui; Chadwick, Dave; Chen, Xinping
Abstract: High input - high output greenhouse vegetable systems are responsible for nutrient surpluses and environmental losses. Integrated strategies that improve soil, crop and nutrient management are needed to ensure more sustainable production systems. We conducted a two-year field experiment to evaluate the potential of integrated soil-crop system management (ISSM) practices to improve the productivity and environmental outcomes from an intensive greenhouse tomato production system in the Yangtze River Basin, China. Four treatments were tested: i) farmers' practice (FP); ii) soil remediation (SR), where lime nitrogen with compost addition was the only management strategy; iii) a treatment that combined soil remediation with optimized crop planting density (SRCO), which increased planting density for improving crop yield; and iv) integrated soil-crop system management (ISSM), as a systematic integrated approach, which included the combined optimization of soil remediation, crop optimization, and nutrient management. In the integrated soil-crop system management treatment, nutrient management was optimized through adoption of the most appropriate type (formula) of fertilizer for the crop, rate and application timing of synthetic fertilizer, and by substituting poultry manure with compost. Our results indicated that the fruit yield of the integrated soil-crop system management treatment was 104 t ha −1, 13.4%–37.3% higher than that of the other three treatments. The mean reactive nitrogen loss (81.1 kg N ha −1 ) and the greenhouse gas emissions (6495 kg CO2 -eq ha −1 ) in the farmers' practice treatment were much higher than in the other three treatments (reactive nitrogen loss: 47.9–54.3 kg N ha −1 ; and greenhouse gas emissions: 4926–5468 kg CO2 -eq ha −1, respectively). The mean nitrogen and carbon footprints of the integrated soil-crop system management treatment were significantly lower than those of other treatments, as a result of both the lower fertilizer nitrogen use and the greater yield. This study indicates that integrated soil-crop system management could produce greater yields and increase net profit with reduced nitrogen inputs, whilst reducing the environmental cost associated with conventional farmers' practice in plastic-greenhouse vegetable production systems. Graphical abstract: Note: FP is the farmers' practice treatment; SR is the soil remediation treatment; SRCO is the soil remediation and crop density optimization treatment; ISSM is integrated soil-crop system management treatment. Image 1 Highlights: Integrated systematic approach (ISSM) increased yield by 37.3% compared to farmers' practice (FP). ISSM increased the net profit (NP) by 49.4% compared to FP. ISSM reduced the carbon (C) footprint by 43.9% with 52.3% less N rate compared to FP. ISSM increased the yield and NP with reducing C footprint, compared to single nutrient management measures.